Two small molecule lead compounds as new antifungal agents effective against Candida albicans and Saccharomyces cerevisiae - Pilehvar-Soltanahmadi, Yones; Panahi, Yasin; Andalib, Sasan; Balaghi-Inalou, Marzieh; Alipour, Shahriar; Moazzez-Lalaklo, Nasim; Sandoghchian-Shotorbani, Siamak; Hatamnejad, Leila Sadat (Novelty in Biomedicine, 2014)
Background: Antifungal drug resistance and few numbers of available drugs limit therapeutic options against fungal infections. The present study was designed to discover new antifungal drugs. Materials and Methods: This study was carried out in two separate steps, that is, in silico lead identification and in vitro assaying of antifungal potential. A structural data file of a ternary complex of fusicuccin (legend), C terminus of H+-ATPase and 14-3-3 regulatory protein (1o9F.pdb file) was used as a model. Computational screening of a virtual 3D database of drug-like molecules was performed and selected small molecules, resembling the functional part of the ligand performing ligand docking, were tested using ArgusLab (4.0.1). Two lead compounds, 3-Cyclohexan propionic acid (CXP) and 4-phenyl butyric acid (PBA) were selected according to their ligation scores. Standard Strains of Candida albicans and Saccharomyces cerevisiae were used to measure the antifungal potential of the two identified lead compounds against the fungi using micro-well plate dilution assay. Results: Ligation scores for CXP and PBA were -9.33744 and -10.7259 kcal/mol, respectively, and MIC and MFC of CXP and PBA against the two yeasts were promising. Conclusion: The evidence from the present study suggests that CXP and PBA possess potentially antifungals properties.